Inhibition of the lectin pathway of complement activation reduces LPS-induced acute respiratory distress syndrome in mice - Ali, Youssif M.; Lynch, Nicholas J.; Shaaban, Ahmed A.; Rizk, Dina E.; Abdel-Rahman, Shaymaa H.; Khatri, Priyanka; Yabuki, Munehisa; Yaseen, Sadam; Dudler, Thomas; Demopulos, Gregory; Schwaeble, Wilhelm J. (Frontiers in Immunology, 2023)
Acute respiratory distress syndrome (ARDS) is a life-threatening disorder with a high rate of mortality. Complement activation in ARDS initiates a robust inflammatory reaction that can cause progressive endothelial injury in the lung. Here, we tested whether inhibition of the lectin pathway of complement could reduce the pathology and improve the outcomes in a murine model of LPS-induced lung injury that closely mimics ARDS in human. In vitro, LPS binds to murine and human collectin 11, human MBL and murine MBL-A, but not to C1q, the recognition subcomponent of the classical pathway. This binding initiates deposition of the complement activation products C3b, C4b and C5b-9 on LPS via the LP. HG-4, a monoclonal antibody that targets MASP-2, a key enzyme in the lectin pathway, inhibited LP functional activity in vitro, with an IC50 of circa 10nM. Administration of HG4 (5mg/kg) in mice led to almost complete inhibition of the lectin pathway activation for 48hrs, and 50% inhibition at 60hrs post administration. Inhibition of the lectin pathway in mice prior to LPS-induced lung injury improved all pathological markers tested. HG4 reduces the protein concentration in bronchoalveolar lavage fluid (p<0.0001) and levels of myeloid peroxide (p<0.0001), LDH (p<0.0001), TNF and IL6 (both p<0.0001). Lung injury was significantly reduced (p<0.001) and the survival time of the mice increased (p<0.01). From the previous findings we concluded that inhibition of the lectin pathway has the potential to prevent ARDS pathology.